Esensi Nilai Ummatan Wasathan sebagai Modal Hidup di Era New Media - Nadea Siti Sa’adah (UIN Sunan Gunung Djati Bandung, 2022)
The new media era has become an era that is widely echoed by the wider community which has many effects, both positive and negative. This study aims to discuss the essence of the wasathan ummatan value as a living capital in the new media era. This study uses a qualitative method based on a literature study that uses content analysis. The results and discussion show the frenzy of the new media era which is currently being